PENGARUH WAKTU DAN SUHU PADA SINTESIS ALUMINIUM FORMAT METAL ORGANIC FRAMEWORK MENGGUNAKAN METODE SOLVOTHERMAL: Indonesia - Aqilla Fadia Haya; Arifin, Zainal; Fitriyana, Fitriyana (Journal of Research and Education Chemistry, 2025)
Beverage cans are generally made of aluminum alloy and recyclable tin steel. Synthesis of aluminum formate metal organic framework (ALF-MOF) from waste cans, which has the potential to produce functional materials for gas storage, catalysis, and gas absorption applications. The solvothermal process involves the reaction between aluminum precursor solution from used beverage cans with organic ligands and solvents. This study aims to determine the effect of reaction time and temperature on the synthesis of ALF-MOF by solvothermal method. The research began by dissolving aluminum metal in beverage cans with NaOH and HCl to produce aluminum hydroxide. Then the synthesis of ALF-MOF was carried out following a one factor at a time (OFAT) experimental design with one variable. Aluminum hydroxide and formic acid were mixed with a mole ratio of 1:3. Next, ethanol-water solvent 1:1 was added as much as 30 mL. The mixture was reacted in an autoclave reactor with reaction time variations of 30, 60, 120, 360, 420 minutes and temperature variations of 80, 90, 100, 110, 120℃. Furthermore, the yield of ALF-MOF product was calculated and analyzed with FTIR instrument to determine the characteristics of its functional groups. The results showed that the optimal time was 360 minutes with a yield of 23.04%, while the best temperature was 100°C with a yield of 23.01%. FTIR analysis identified Al-O-Al groups at wave numbers 1089-1092 cm-¹, indicating the success of ALF-MOF synthesis.